Reformulation of the Indonesian Criminal Code (KUHP) Number 1 of 2023 Article 445 Paragraph (1) Item 1: A Lawrence Friedman’s Theory of Justice Perspective Toward a Responsive and Culture-Oriented Criminal Law - Jumain Azizi; Roibin Roibin; Zaenul Mahmudi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze Article 445 paragraph (1) of the Indonesian Criminal Code (KUHP) Number 1 of 2023, which regulates the criminal act of eloping with a young woman. The provision is considered to be in tension with the social and cultural realities of Indonesian society, particularly the people of Lombok who practice the merariq tradition. Merariq is an ancestral customary practice within marriage rituals involving the consensual elopement of the prospective bride as an integral part of the marriage process. This research uses Lawrence M. Friedman’s legal system theory, which examines three main components of law: (1) the substance of law—normative provisions contained in legislation; (2) the structure of law institutions and law enforcement agencies; and (3) the legal culture values, attitudes, and behavior of society toward law. This study is a normative legal research that treats law as norms, principles, doctrines, and rules. The primary legal material is Article 445 paragraph (1) of the Indonesian Criminal Code. The findings indicate that, from the perspective of legal substance, the article remains ambiguous. Its formulation potentially conflicts with Indonesia’s legal culture, which in practice prioritizes familial and traditional mechanisms for resolving private conflicts. Based on these findings, this study recommends a reformulation of the legal substance to make it more responsive to the socio-cultural context. The reformulation should be grounded in the principles of ultimum remedium and restorative justice, providing space for customary law and local culture as legitimate mechanisms to resolve private disputes. This approach is expected to reduce the disproportionate use of imprisonment and position criminal sanctions as a last resort in law enforcement.